Small bowel incarceration as a complication of port site drainage following laparoscopic hysterectomy - Ljuština, Saša R; Sparić, Radmila M; Novaković, Sanja M; Buzadžić, Snežana N (Vojnosanitetski pregled, 2014)
Introduction. Indication for surgical drainage may be prophylactic or therapeutic. However, surgical drains may cause complications. These complications can arise either following laparoscopic or open surgery. One of the rare complications resulting from drainage includes herniation of abdominal viscera at the drain site. The most common herniated abdominal organ is the small bowel. Case report. A 75-year-old woman underwent laparoscopic hysterectomy for atypical endometrial hyperplasia. After the operation, she developed small bowel herniation in the abdominal wall at the drain site, which was confirmed by multislice computed tomography. The patient underwent emergency relaparotomy that identified drain site incarceration of an ileal loop. Following resection of the incarcerated bowel, her postoperative recovery was uneventful. Conclusion. This case presents rare causative mechanism of intestinal obstruction. The possible occurrence of hernias following surgical drainage must be kept in mind.
Keywords: drainage; hysterectomy; laparoscopy; postoperative period; hernia; intestine; small; abdominal wall